Over 4, 500 years of trepanation in Poland: From the unknown to therapeutic advisability. (31st May 2018) - Lorkiewicz, W.; Mietlińska, J.; Karkus, J.; Żądzińska, E.; Jakubowski, J. K.; Antoszewski, B.
Abstract: This paper discusses 6 trepanned skulls from central Poland, dating from the late Neolithic (3, 000–2, 800 BC ) to early modern times (18th century AD). Four of them come from a small area in and around the town of Brześć Kujawski in Kujawy, a region of long‐lasting and intense human settlement in Poland. The analysed skulls provide striking evidence for the long history of trepanation in this part of Europe. Three surgical techniques were used: sawing, scraping, and drilling, either on their own or in combination with one another. Regardless of the method, all the trepanations were fully healed, which proves long‐term survival of the patients. All skulls belonged to adult males, who were generally at a higher risk of trauma in the populations from which 4 of the specimens derive. The studied skulls demonstrate a marked evolution in trepanation practices over time. Trepanations from the late medieval and early modern times tend to be smaller, less life threatening, and clearly made for therapeutic purposes to remedy cranial injuries. The remarkable skills of the surgeons who performed them could be linked to the influence of the renowned Danzig Anatomical School in Gdańsk, which was one of the leading centres of medical and anatomical research in northern and central Europe in the 17th and 18th centuries.